Determination of Vegetation Cover Loss Using Remote Sensing in Padre Abad from 2005 to 2025 - Martínez Molina, Giovanna Madeleyne; Poma Carbajal, Edwin Favián; Navarro Reynalte, Hillary Anais; Burga Beteta, Luciana Andrea; Ybarra Suárez, Liset Maicela; Garbozo Picasso, Luzmaria Andrea; Alcantara Chugnas, Nayeli Yamile (LACCEI, 2025)
Abstract-The purpose of this project, entitled “Determining vegetation cover loss through remote sensing in Padre Abad from 2005 to 2025,” is to identify, quantify, and analyze changes in vegetation cover in the province using multi-temporal satellite images processed with GIS tools such as QGIS and Python. This research responds to the alarming loss of primary forests in the region, driven by human activities such as shifting cultivation, logging, illicit crops, and legal agricultural expansion. Through the analysis of satellite images from the years 2005, 2010, 2015, 2019, and 2025, the study seeks to visualize patterns of deforestation and vegetation recovery, generating thematic maps and statistics that serve as a basis for sustainable territorial planning. The project provides scientific evidence for environmental decision-making and promotes the use of accessible technologies for landscape monitoring in vulnerable areas.